2002
DOI: 10.1164/ajrccm.165.8.2106110
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Thymus- and Activation-regulated Chemokine in Bronchoalveolar Lavage Fluid from Patients with Eosinophilic Pneumonia

Abstract: Thymus- and activation-regulated chemokine (TARC/CCL17) is a lymphocyte-directed CC chemokine, which plays a role in the recruitment of CC chemokine receptor-4 positive T helper 2 (Th2) cells. In this study, we measured concentrations of TARC and Th2 cell-derived cytokines in bronchoalveolar lavage (BAL) fluid, as well as TARC concentrations in serum from patients with eosinophilic pneumonia and other interstitial lung diseases. TARC was significantly elevated in BAL fluids from patients with eosinophilic pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 41 publications
4
62
2
Order By: Relevance
“…As in CEP, the chemokine CCL17 has been detected in high levels in AEP, potentially consistent with a role for recruited T cells in the pathogenesis of AEP (114). An array of both Th2 and Th1 cytokines are elevated in the BAL fluid in AEP, including IL-1ra, IL-2, IL-5, IL-10, IL-12, IL-13, and IL-18, perhaps reflecting the known pluripotent secretory potential of eosinophils (3,76,180).…”
Section: Aepmentioning
confidence: 55%
See 1 more Smart Citation
“…As in CEP, the chemokine CCL17 has been detected in high levels in AEP, potentially consistent with a role for recruited T cells in the pathogenesis of AEP (114). An array of both Th2 and Th1 cytokines are elevated in the BAL fluid in AEP, including IL-1ra, IL-2, IL-5, IL-10, IL-12, IL-13, and IL-18, perhaps reflecting the known pluripotent secretory potential of eosinophils (3,76,180).…”
Section: Aepmentioning
confidence: 55%
“…BAL fluid in CEP contains the cytokines IL-4, IL-5, IL-6, IL-10, IL-13, and IL-18, which is largely consistent with local Th2 inflammation, though the Th1 cytokines IL-2 and IL-12 are present as well (76,85,114). Several chemokines are also present in BAL fluid samples, including CCL17 and CCL22, the chemokine ligands of the receptor CCR4, suggesting that T cell recruitment may be an important factor in the pathophysiology of CEP (74,114). In addition, CXCL9, CXCL10, CCL5 (RANTES), CCL11 (eotaxin-1), CCL2, and CCL4 have also been observed to be elevated in CEP (73,75,89,186).…”
Section: Cepmentioning
confidence: 89%
“…This supports a role for these CC chemokines in the development of fibrosis. Previous researchers have shown that CCL17 is elevated in BAL fluid of patients with eosinophilic pneumonia that correlated with the presence of IL-4, IL-5, and IL-13 in BAL fluid (33). Similarly Katoh et al (34) have shown that CCR4 ϩ CD4 ϩ T cells in BAL fluid from patients with eosinophilic pneumonia correlated with BAL fluid levels of CCL17, CCL22, and IL-5.…”
Section: Discussionmentioning
confidence: 75%
“…CCL22 and CCL17 belong to a CC chemokine family and are involved in several Th2-dominant diseases, such as bronchial asthma, atopic dermatitis and eosinophilic pneumonia [22][23][24][25]. These two chemokines are the specific ligands of CCR4 [10] and are pivotal in recruiting Th2 to sites of inflammation under Th2-dominant conditions.…”
Section: Discussionmentioning
confidence: 99%